TECHNOLOGY FOR ACCURACY EVALUATION OF BEGGINER TABLE TENNIS PLAYER (Fiep Bulletin - online, 2013)
The objective of this scientific investigation operate between  March 2010-October 2011 -was to determine the possibility of using the table tennis robot and the contact sensors as a means of evaluating the precision, in order to transform them into a working tool for the researchers, teachers or coaches who need to identify and quantify these movement qualities. At this study was participate 63 subjects between 9-10 years old, from 6 tennis table associations from Romania.  This study was coordinated by Faculty of Health, Sports and Movement Science. The accuracy level of the execution has been established by administrating a control test made up of 6 types of exercises (control of forehand and backhand stroke, play with forehand and backhand stroke and service); the processing of the data and the graphical display have been made on a Toshiba A2 notebook, using a data base similar to Excel. Besides the accuracy of information (the robot excludes the influence of the human factor), the system also offers the possibility of testing a large number of subjects in a relatively short period of time. The graphical display of the results in real time offers the possibility to correct and improve the weak parameters.
Keywords: technology; evaluation; tennis table